2014
DOI: 10.3329/ijarit.v3i2.17842
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro studies of some selected botanicals and baubiofungicide on mycelial growth and conidial germination of Cercospora arachidicola and Cercosporidium personatum

Abstract: Efforts have been made to assess some plant extracts namely, Lycopersicon esculentum, Tagetus patula, Achras sapota, Azadirachta indica, Datura metel, Cymbopogon citrates, Polyalthia longifolia, Allium sativum and Allium cepa in vitro for the management of leaf spot (tikka) disease of groundnut cultivar Dhaka-1 caused by Cercospora arachidicola and Cercosporidium personatum. Results indicated that all the tested plant extracts and BAUBiofungicide suppressed the growth of mycelium and inhibition of conidial ger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
(6 reference statements)
1
1
0
Order By: Relevance
“…Trichoderma based BAU bio-fungicide also showed the positive effect on plant growth parameters, however; the effect was less in compare with PGP hormone and Carbendazim treatment. Several studies also reported that plant height and weight increased with BAU bio-fungicide in different vegetables [22] and in this study, BAU bio-fungicide (seed treatment followed by spray) averagely increased plant height from 59.75 to 67.84 cm in both varieties. In lettuce, Yedicula cultivar with the application of Tricoderma in per peat number of leaf calculated 3.8 to 4.3, hypocotyls length measured 5 to 8.5 cm, and seedling fresh weight found 3.8 to 4.3 gm at 15 gm/m 2 dosages and root weight resulted 0.18 to 0.28 gm at 10gm/m 2 dosages [23].…”
Section: Discussionsupporting
confidence: 69%
“…Trichoderma based BAU bio-fungicide also showed the positive effect on plant growth parameters, however; the effect was less in compare with PGP hormone and Carbendazim treatment. Several studies also reported that plant height and weight increased with BAU bio-fungicide in different vegetables [22] and in this study, BAU bio-fungicide (seed treatment followed by spray) averagely increased plant height from 59.75 to 67.84 cm in both varieties. In lettuce, Yedicula cultivar with the application of Tricoderma in per peat number of leaf calculated 3.8 to 4.3, hypocotyls length measured 5 to 8.5 cm, and seedling fresh weight found 3.8 to 4.3 gm at 15 gm/m 2 dosages and root weight resulted 0.18 to 0.28 gm at 10gm/m 2 dosages [23].…”
Section: Discussionsupporting
confidence: 69%
“…Other management practices in the developing countries include seed treatment with non-conventional chemicals (Maiti et al 2005), cultural practices by adjusting sowing times (Naidu and Vasanthi 1995), and through use of biological control agents (Kishore and Pande 2005) and botanicals (Hossain and Hossain 2013). Multiple applications of chemical fungicides offer quick and effective remedy for these diseases.…”
Section: Introductionmentioning
confidence: 99%